Application of Forc Distributions to the Study of Magnetic Interactions in Co-Doped batio3 Nanomaterials - Barraza-Aguilera, N (Elsevier Ltd, 2018)
Co-doped BaTiO3 (BT) nanomaterials were synthesized by a combination of sol-gel and hydrothermal methods under an oxygen partial pressure of 200 psi. The surface chemistry of the samples and, in particular, the oxidation state of the Co atoms, was investigated by X-ray photoelectron spectroscopy, while X-ray powder diffraction and Raman spectroscopy were used to obtain structural information. Morphological information was acquired by atomic force microscopy. The dependence of the magnetic properties of the samples as a function of Co-doping level in BT and the effect of the base used in the synthesis of the compound (i.e. NaOH or KOH) was studied from the analysis of hysteresis curves and FORC diagrams. The results demonstrated that the level of ferromagnetic component tend to increases as the percentage of Co doping is decreased. © 2017 Elsevier B.V.